Current Status and Future Development of Cell Transplantation Therapy for Periodontal Tissue Regeneration - Toshiyuki Yoshida; Kaoru Washio; Takanori Iwata; Teruo Okano; Isao Ishikawa (International Journal of Dentistry)
It has been shown that stem cell transplantation can regenerate periodontal tissue, and several clinical trials involving transplantation of stem cells into human patients have already begun or are in preparation. However, stem cell transplantation therapy is a new technology, and the events following transplantation are poorly understood. Several studies have reported side effects and potential risks associated with stem cell transplantation therapy. To protect patients from such risks, governments have placed regulations on stem cell transplantation therapies. It is important for the clinicians to understand the relevant risks and governmental regulations. This paper describes the ongoing clinical studies, basic research, risks, and governmental controls related to stem cell transplantation therapy. Then, one clinical study is introduced as an example of a government-approved periodontal cell transplantation therapy.